Re-usable Post Operative Lower Leg Supports - Brule, Andrew (CMBES Proceedings, 2014)
Sunny Hill Health Centre for Children (SHHCC) is British Columbia’s (BC) referral centre for children with disabilities. For decades SHHCC’s Positioning and Mobility Team (PMT) have been called to BC’s Children’s Hospital (BCCH) for emergency post-operative positioning for children confined to mobility aids having just had lower leg surgeries (i.e. hip adductor release, de-rotational osteotomy, hamstring release, etc…). Post-operatively, physicians usually require the client’s leg(s), often in casts, to be abducted and elevated in specific positions for them to leave bed and become mobile as soon as possible. This required expensive, labour intensive custom solutions for each client. SHHCC’s PMT developed a low cost (150 each), adjustable, reusable lower leg support that can be mounted on the client’s own mobility aid. Using the client’s mobility aid reduces client anxiety, eliminates the need to transfer life support equipment, and reduces the hospital’s requirement to stock and maintain mobility aids. The leg supports reduce the knowledge, skill, labour and costs required to implement a lower leg support and allows the client to be transferred to the community as soon as medically stable. Furthermore, the leg supports’ position are easily adjustable which enables the community team to change their position as the client’s recovery progresses. When the client has recuperated, the community team can remove the system and return it to the hospital for sterilization and re-use leaving the client’s wheelchair untouched for easy adaptation to the client’s new lower leg and hip position. This device has been in clinical use since 2008.